-6(2x+8)=4x

Simple and best practice solution for -6(2x+8)=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2x+8)=4x equation:


Simplifying
-6(2x + 8) = 4x

Reorder the terms:
-6(8 + 2x) = 4x
(8 * -6 + 2x * -6) = 4x
(-48 + -12x) = 4x

Solving
-48 + -12x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-48 + -12x + -4x = 4x + -4x

Combine like terms: -12x + -4x = -16x
-48 + -16x = 4x + -4x

Combine like terms: 4x + -4x = 0
-48 + -16x = 0

Add '48' to each side of the equation.
-48 + 48 + -16x = 0 + 48

Combine like terms: -48 + 48 = 0
0 + -16x = 0 + 48
-16x = 0 + 48

Combine like terms: 0 + 48 = 48
-16x = 48

Divide each side by '-16'.
x = -3

Simplifying
x = -3

See similar equations:

| z=(x-77.5)/11.6 | | 4v/2=-10 | | e^7x+2=15 | | 9x+3=4x+1 | | 2(x+5)=3x-18 | | 3cos^3(x)=3cos(x) | | x+4(3)=x+2(5) | | 6d-5-d= | | 15x+80x-10=19(5x+15) | | C/4-3=8 | | -.6t^2+4.8t=0 | | 0=4x^2+25x-21 | | 1.5-5x=11.0 | | 4y+x=-12 | | n+19=13 | | (2x^2-6x+7)-(4x^2+x-9)+(5x^2+3x-8)= | | -3(3x-6)=-9x-18 | | 0=-5T^2+37t+72 | | y=2x^2-3x+6 | | 8-8x-x^2=0 | | (2-2y+4u)(-9)= | | 0=4x^2+32x+15 | | Y-3=5-2y | | 10x+8.25=99 | | lx-3l=5x-5 | | 5x=x-14 | | 3x+y=10x-1 | | 8.25+10=99 | | W+0.04W=10.92 | | H(1)=-4.9(1)t^2+7(1)+0.6 | | (-4x+5)(-2x+7)= | | 6x+3y+8z=54 |

Equations solver categories